How Late to Pay? Understanding Wage Arrears in Russia - Earle, John S.; Sabirianova, Klara Z. (Journal of Labor Economics, 2002)
We organize an empirical analysis of Russian wage arrears around hypotheses concerning incentives for firms to pay late and for workers to tolerate late payment. Nationally representative household panel data matched with employer data show that arrears are positively related to firm age, size, state ownership, and declining performance. Constrained multinomial logit estimates reveal intrafirm variation related to job tenure and small shareholdings in the firm. Wage arrears, unlike wage cuts, have a theoretically ambiguous effect on workers' quit behavior, and we show empirically that the effect varies negatively with the extent of the practice in the local labor market.